In vitro selection of drought-tolerant white poplar clones based on antioxidant activities and osmoprotectant content - Vuksanović, Vanja; Kovačević, Branislav; Kebert, Marko; Pavlović, Lazar; Kesić, Lazar; Čukanović, Jelena; Orlović, Saša (Frontiers in Plant Science, 2023)
In light of upcoming climate change, there is an urgent requirement for tree improvement regarding adaptability to drought-caused stress and the development of quick and reliable screening methodologies for genotypes’ drought tolerance. White poplar is, despite its high adaptability, considered to be an endangered tree species in Serbia, which gives it special importance in the preservation and improvement of biodiversity of riparian ecosystems. The main goal of this research was to evaluate the tolerance of five white poplar clones to the presence of polyethylene glycol (PEG 6000 molecular weight 6000) (different concentrations (e.g. 0 g/L, 1 g/L, 10 g/L, 20 g/L, and 50 g/L) in Aspen Culture Medium (ACM). The tolerance of the clones was evaluated by using morphological parameters (shoot fresh and dry weight, root fresh and dry weight), photosynthetic pigments (contents of chlorophyll a, chlorophyll b, carotenoids, and chlorophyll a+b), and biochemical parameters (total phenolic content, total flavonoid content, ferric reducing antioxidant power, antioxidant activities (DPPH activity and ABTS assay), free proline content and glycine betaine content. The values of morphological and photosynthetic pigments declined with an increase in the concentration of PEG 6000. At a concentration of 50 g/L, the content of shoot fresh mass decreased by 41%, the content of Chl a by 68%, Chl b by 65%, and Car by 76% compared to the control. Also, at the same medium, there was an increase in the content of total phenols, accumulation of proline, the content of glycine betaine as well as in antioxidant activity. Based on the obtained results, it can be assumed that more drought-tolerant clones are characterized by high values for biomass, high content of photosynthetic pigments, and high content of proline and glycine betaine in conditions similar to drought in vitro. Clone L-80 showed better results in most of the tested parameters, especially compared to the reference clone Villafranca.